2017
DOI: 10.1016/j.cub.2016.11.041
|View full text |Cite
|
Sign up to set email alerts
|

Neurons Responsive to Global Visual Motion Have Unique Tuning Properties in Hummingbirds

Abstract: Neurons in animal visual systems that respond to global optic flow exhibit selectivity for motion direction and/or velocity. The avian lentiformis mesencephali (LM), known in mammals as the nucleus of the optic tract (NOT), is a key nucleus for global motion processing [1-4]. In all animals tested, it has been found that the majority of LM and NOT neurons are tuned to temporo-nasal (back-to-front) motion [4-11]. Moreover, the monocular gain of the optokinetic response is higher in this direction, compared to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 51 publications
0
40
0
Order By: Relevance
“…Alternatively, evolutionary changes in visual acuity, changes in the visual environment through which a bird flies, changes in how that environment is perceived, and changes in how the optical sensory afferents are processed by the brain (Gaede et al. ) might be equally as important as labyrinth morphology for maintaining adequate head stabilisation reflexes. For example, Wylie & Frost () demonstrated that the spatial planes of the optokinetic system of birds are organised with respect to the eye muscles rather than the semicircular canals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, evolutionary changes in visual acuity, changes in the visual environment through which a bird flies, changes in how that environment is perceived, and changes in how the optical sensory afferents are processed by the brain (Gaede et al. ) might be equally as important as labyrinth morphology for maintaining adequate head stabilisation reflexes. For example, Wylie & Frost () demonstrated that the spatial planes of the optokinetic system of birds are organised with respect to the eye muscles rather than the semicircular canals.…”
Section: Discussionmentioning
confidence: 99%
“…This recently has been shown to be potentially unique in vertebrates in that it has rapid sensitivity to relative changes in global scene features in all directions (Gaede et al. ; this region in other tetrapods is more sensitive to front‐to‐back motion of the global visual field). This highlights the potential importance of global visual motion for control of balance in flight, and indicates that evolutionary adaptation of the optokinetic response may be of critical importance in the evolution of tetrapod locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…In nearly all tetrapods studied to date, the typical pattern observed is that LM neurons prefer temporo‐nasal (back‐to‐front) motion across the retina, and nBOR neurons prefer naso‐temporal (front‐to‐back), upward or downward motion (Fite, ; Hoffmann & Schoppmann, ; Ibbotson, Mark, & Maddess, ; Mckenna & Wallman, ; Mustari & Fuchs, ; Winterson & Brauth, ; Wylie & Crowder, ). However, in hummingbirds, a different pattern of response properties in the LM emerged (Gaede, Goller, Lam, Wylie, & Altshuler, ). The majority of LM neurons do not prefer temporo‐nasal motion; instead, there is a more uniform distribution of preferred directions, with cells preferring upward, downward, and naso‐temporal motion as frequently as temporo‐nasal motion (Gaede et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in hummingbirds, a different pattern of response properties in the LM emerged (Gaede, Goller, Lam, Wylie, & Altshuler, ). The majority of LM neurons do not prefer temporo‐nasal motion; instead, there is a more uniform distribution of preferred directions, with cells preferring upward, downward, and naso‐temporal motion as frequently as temporo‐nasal motion (Gaede et al, ). Consistent with other tetrapods, there is a strong population‐level preference for temporo‐nasal motion among LM neurons of zebra finches and pigeons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation